Analisis Isi Penggunaan Facebook dalam Marketing dan Branding Produk Kecantikan Scarlett dan Skin Dewi - Yusril Zafallah; Kunto Adi Wibowo; Ikhsan Fuady (Mahesa Research Center, 2022)
Beauty companies Skin Dewi and Scarlett use social media Facebook to promote their products and to interact with consumers. This article examines and discusses how beauty brands use social media, especially Facebook, to increase brand awareness and brand loyalty with viral marketing theory. This study took 159 samples taken by purposive sampling technique. Of the two brands, uploading content about products is the type of upload that is most uploaded. However, the product promotion technique that is often used looks different, Scarlett uses a giveaway technique, while Skin Dewi uses another technique. The two brands also did not specify a specific time to upload their promotions. In terms of engagement, there is a significant difference between the Scarlett and Skin Dewi brands. Brand Scarlett tends to have good and stable engagement, while Skin Dewi has poor engagement.